Rethinking Violence and Learning: Moving Research into Practice - Susan Heald; Jenny Horsman (Adult Education Research Conference, 2000)
Drawing on focus groups, interviews and participant observation, we explore the ways discourses of violence and of schooling impede efforts to develop literacy programs which respond to the violence and trauma women learners have experienced.